2010
DOI: 10.1002/cmdc.200900499
|View full text |Cite
|
Sign up to set email alerts
|

The Tunable Functionality of α,β‐Unsaturated Carbonyl Compounds Enables Their Differential Application in Biological Systems

Abstract: alpha,beta-Unsaturated carbonyl compounds as potential drug candidates is a controversial topic since their potential Michael acceptor activity can lead to cell damage and cytotoxicity. Nevertheless, the alpha,beta-unsaturated carbonyl functionality can be employed as a tool to fine tune biological activity by directly manipulating this entity. Depending on their electronic properties, alpha,beta-unsaturated carbonyl functionalities display different reactivities, namely Michael addition, radical scavenging, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
96
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(98 citation statements)
references
References 45 publications
0
96
0
Order By: Relevance
“…The 2D QSAR study shown that potency of compounds is well correlated with estimated lipophilicity. Even Michael acceptor comprising molecules are commonly flagged as less than optimal leads, due to its potential promiscuity and consequent toxicity, accumulated examples, reported recently [6], of using ketovinyl moiety as a warhead for directed and selective covalent inhibition of diverse pharmacological targets trigger our interest to further evaluate previous findings. Recently reported suicide inhibitor [7] that selectively target proteosome of HIV infected cells, bear ketovinyl moiety as covalent warhead.…”
Section: Introductionmentioning
confidence: 98%
“…The 2D QSAR study shown that potency of compounds is well correlated with estimated lipophilicity. Even Michael acceptor comprising molecules are commonly flagged as less than optimal leads, due to its potential promiscuity and consequent toxicity, accumulated examples, reported recently [6], of using ketovinyl moiety as a warhead for directed and selective covalent inhibition of diverse pharmacological targets trigger our interest to further evaluate previous findings. Recently reported suicide inhibitor [7] that selectively target proteosome of HIV infected cells, bear ketovinyl moiety as covalent warhead.…”
Section: Introductionmentioning
confidence: 98%
“…Michael acceptors are capable of forming irreversible bonds with biological macromolecules such as proteins or DNA [11][12][13][14][15]. Thus, the ability of salvinorin A-derived Michael acceptors to form covalent bonds may be advantageous for probing the affinity to the KOR.…”
Section: Introductionmentioning
confidence: 99%
“…Enones are of importance since they interfere with the thiol-regulated activation of NF-κB through Michael additions. 31 On the protein level, the enzyme activity of iNOS can be blocked with CO by either inhibiting the formation of the active dimeric form 29 of iNOS or binding of CO to the iron center of the heme prosthetic group. 32 This leads to the deterioration of its catalytic activity to produce NO (Fig.…”
Section: Biological Activitymentioning
confidence: 99%